Ferlina Penerapan Budaya 5S Berbasis Pendidikan Agama Islam Untuk Menumbuhkan Sikap Pluralisme Siswa SMPN 2 Selomerto - Bambang Sugiyanto; Ferlina Nurlitasari; Robingun Suyud El Syam (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
This study aims to: 1) describe the 5S culture based on Islamic Religious Education (PAI) at SMP Negeri 2 Selomerto Wonosobo, 2) determine the condition of pluralism attitudes among students before and after the implementation of the 5S culture based on PAI, and 3) analyze how the implementation of this culture fosters pluralism attitudes among students. This study uses a descriptive research type with a qualitative field approach. Data collection techniques were carried out through in-depth interviews with PAI teachers and students, direct observation at school, and documentation. Data were analyzed using the Miles and Huberman technique through data reduction, data presentation, and drawing conclusions. The results of the study indicate that: 1) the implementation of the 5S culture based on PAI has been integrated into school activities through the habit of morning greetings, smiles, greetings, and moral guidance in PAI learning; 2) students' pluralism attitudes have increased, marked by the ability to work together, positive interactions, and reduced potential for conflict between students; 3) the 5S culture based on PAI contributes to fostering pluralism attitudes through the habit of manners, respect, and inclusive communication. Supporting factors include teacher role models and school habits, while obstacles include external environmental influences and a lack of consistent standards.